Central Sympathetic Modulation Reverses Microvascular Alterations in a Rat Model of High‐Fat Diet‐Induced Metabolic Syndrome. (May 2016) - Nascimento, Alessandro R.; Machado, Marcus V.; Gomes, Fabiana; Vieira, Aline B.; Gonçalves‐de‐Albuquerque, Cassiano F.; Lessa, Marcos A.; Bousquet, Pascal; Tibiriçá, Eduardo
Abstract: Objectives: The objective of this study was to investigate the role of the SNS on hemodynamic, metabolic, and microvascular alterations in a rat model of HFD‐induced MS with salt supplementation. Methods: In total, 40 adult male Wistar rats were fed normal chow ( n = 10) or a HFD ( n = 30) for 20 weeks. Thereafter, the HFD group received the centrally acting sympatho‐modulatory drugs clonidine (0.1 mg/kg) or rilmenidine (1 mg/kg) or vehicle ( n = 10/group) orally by gavage. FCD was evaluated using intravital video microscopy, and the SCD was evaluated using histochemical analysis. Results: The pharmacological modulation of the SNS induced concomitant reductions in SBP, HR and plasma catecholamine levels. These effects were accompanied by a reversal of functional and structural capillary rarefaction in the skeletal muscle in both treated groups and an increase in SCD in the left ventricle only in the rilmenidine group. Improvement of the lipid profile and of glucose intolerance was also obtained only with rilmenidine treatment. Conclusions: Modulation of sympathetic overactivity results in the reversal of microvascular rarefaction in the skeletal muscle and left ventricle and improves metabolic parameters in an experimental model of MS in rats.